Analisis Keuangan 11 Perusahaan Non-Finansial yang Terdaftar di Bei Sebelum dan Sesudah Melakukan Akuisisi di Tahun 2025 - Yosep Eka Putra; Intan Salsabilla; Dhilsy Faisya Azzahra; Diva Avivah; Claudea Amanda (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to assess the financial performance of 11 non-financial companies that conducted acquisitions in 2025 and are listed on the Indonesia Stock Exchange (IDX). Using a quantitative descriptive-comparative approach with a case study design, six financial ratios were analyzed: Current Ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return on Assets (ROA), and Return on Equity (ROE). Data were obtained from consolidated financial statements as of December 31, 2024 (pre-acquisition) and December 31, 2025 (post-acquisition). The results show that the impact of acquisitions varies across companies. No consistent or significant differences were found in the CR, DAR, DER, ROA, or ROE ratios between the two periods. Meanwhile, the TATO ratio tended to decrease after the acquisition, indicating that the newly consolidated assets have not yet operated optimally. These findings confirm that the short-term financial impact of an acquisition is heavily influenced by the transaction’s funding structure, the size of the acquired entity, and the industry sector. This study contributes to the financial accounting literature on corporate acquisition strategies in the Indonesian capital market.